Prevalence and associated risk factors of bovine Schistosoma and Fasciola infections among cattle in South Achefer District, North West Ethiopia - Solomon Tesfaye; Mastewal Yeshambel; Amir Alelign; Tilahun Yohannes (Parasite Epidemiology and Control)
Bovine schistosomiasis and fasciolosis, caused by flatworms from different species of Schistosoma and Fasciola, continue to be significant animal health concerns in cattle farming in developing countries like Ethiopia. However, not enough epidemiological information is available in most parts of Ethiopia in this respect. Therefore, the present study aimed to determine the magnitude of these two important zoonotic diseases and the associated risk factors in south Achefer district, northwest Ethiopia. A cross-sectional study was carried out in June and August of 2020. The research cattle, which belonged to farmers in three selected localities, were chosen by a simple random sampling method. Freshly collected faecal samples were subjected to a parasitological test using the sedimentation technique to identify eggs of Schistosoma and Fasciola. We used Pearson's chi-square (χ2) test to ascertain the degree of variation between the proportions of disease occurrence. Logistic regression analyses were performed for the risk factor analysis. The overall prevalence of Schistosoma bovis and Fasciola hepatica was 9.6 % (37/384) and 54.2 % (208/384), respectively. Cross-bred cattle had around twice the odds of contracting Fasciola hepatica than local cattle (adjusted odds ratio, AOR: 1.87, 95 % CI: 1.02–3.43). The prevalence of Fasciola hepatica was more than seven times higher in younger cattle than in older cattle (AOR: 7.31, 95 % CI: 3.54–15.08). Comparatively to cattle in good physical health, those in poor physical condition were shown to contract Fasciola hepatica more than four times (AOR: 4.85, 95 % CI: 1.94–12.14). This study indicated that bovine Schistosoma and Fasciola infections remain among the major cattle health problems in the study area. Therefore, appropriate intervention methods should be implemented for effective zoonotic disease control in the study area.